The realism of assumptions does matter: Why Keynes-Minsky theory must replace efficient market theory as the guide to financial regulation policy - James Crotty (University of Massachusetts, Department of Economics, 2011)
The radical deregulation of financial markets after the 1970s was a precondition for the explosion in size, complexity, volatility and degree of global integration of financial markets in the past three decades. It therefore contributed to the severity and breadth of the recent global financial crisis. It is not likely that deregulation would have been so extreme and the crisis so threatening had most financial economists adopted Keynes-Minsky financial market theory, which concludes that unregulated financial markets reinherently unstable and dangerous. Instead, they argued that neoclassical efficient financial market theories demonstrate that lightly regulated generate optimal security prices and risk levels, and prevent booms and crashes. Efficient market theory became dominant in spite of the fact that it is a fairly-tale theory based on crudely unrealistic assumptions. It could only have been adopted by a profession committed to Milton Friedman's fundamentally flawed positivist methodology, which asserts that the realism of assumptions has no bearing on the validity of a theory. Keynes argued persuasively that only realistic assumptions can generate realistic theories. Keynes-Minsky theory, which is derived from a realistic assumption set, should be the profession's guide to regulation policy.
Keywords: B41; B5; G10; G11; G12; 330; efficient financial market theory; Keynes-Minsky financial theory; Friedman's positivism; financial regulation; financial crises